Stabilization of carbon black particles with Cetyltrimethylammoniumbromide in aqueous media - Eisermann, Claudia; Damm, Cornelia; Winzer, Bettina; Peukert, Wolfgang (Powder Technology, 2014)
The stabilization mechanism of aqueous carbon black suspensions by Cetyltrimethylammoniumbromide (CTAB) is studied in this paper. The adsorption of the surfactant CTAB on the carbon black particles was investigated on dried samples by thermogravimetric analyses (TGA), nitrogen adsorption and attenuated total reflection Fourier transformation infrared spectroscopy (ATR-FTIR) as well as in suspension by zeta potential measurements and atomic force microscopy. The particles are stabilized by an adsorbed CTAB monolayer as can be concluded from the results of TGA and of AFM investigations using a liquid cell. Extended DLVO calculations including the steric contribution of CTAB reveal that carbon particles with an adsorbed monolayer of CTAB exhibit sufficient colloidal stability. This result is in qualitative agreement with the experimental results. © 2013 Elsevier B.V.
Keywords: Carbon black; CTAB adsorption; Dispersion; DLVO calculations; Electrosteric stabilization